The Effect of Feedstock Concentration on the Microbial Community Dynamics During Textile Waste Composting - Biyada, Saloua; Merzouki, Mohammed; Dėmčėnko, Taisija; Vasiliauskienė, Dovilė; Marčiulaitienė, Eglė; Vasarevičius, Saulius; Urbonavičius, Jaunius (Frontiers in Ecology and Evolution, 2022)
In the current study, the effect of initial feedstock concentration on the microbial communities structure and dynamics during textile waste composting processes was investigated using the next-generation sequencing approach. For this, three mixtures were prepared with different textile waste concentrations mixed with green waste and paper & cardboard waste for composting, to choose the proportion that will provide a mature final compost. A comprehensive characterization of the microbial communities associated with different textile waste concentrations during composting was achieved. It was noted that by increasing the concentration of textile waste, microbial communities (bacterial and fungal) change. Genera and species belonging to Actinobacteria, Firmicutes, Chloroflexia, Rozellomycota, Mortierellomycota, Aphelidiomycota, Ascomycota and Mucoromycota were the most abundant in the mixtures containing either 40% or 60% of textile waste whereas some of species were absent at 80% of textile waste in the mix; this difference was also refelected by their enzymatic activities. Generally, these phyla are associated with composting, and they play a major role in recalcitrant molecular decaying. Ultimately, it can be concluded that the shift most likely occurred in microbial communities during composting probably owing to the interaction between changes in the nutrient concentration and microbial communities. This investigation proves that the concentration of textile waste significantly affects the microbial communities and demonstrate that a high concentration of textile waste is not suitable to grant a good maturity of compost.